2013
DOI: 10.1371/journal.pone.0073489
|View full text |Cite
|
Sign up to set email alerts
|

Pseudophosphorylated αB-Crystallin Is a Nuclear Chaperone Imported into the Nucleus with Help of the SMN Complex

Abstract: The human small heat shock protein αB-crystallin (HspB5) is a molecular chaperone which is mainly localized in the cytoplasm. A small fraction can also be found in nuclear speckles, of which the localization is mediated by successional phosphorylation at Ser-59 and Ser-45. αB-crystallin does not contain a canonical nuclear localization signal sequence and the mechanism by which αB-crystallin is imported into the nucleus is not known. Here we show that after heat shock pseudophosphorylated αB-crystallin mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(65 reference statements)
0
19
0
Order By: Relevance
“…Analysis of the CG43851 sequence predicts nuclear or cytoplasmic localization depending on the prediction tool used (Euk-mPLoc 2.0 (Chou and Shen 2010 ), SLP-Local (Matsuda et al 2005 ), CELLO v2.5 (Yu et al 2006 ), Sherloc2 ), MultiLoc2 . In mammals, all sHsps are mainly located in the cytoplasm but some shuttle to the nucleus or to the mitochondria (Bryantsev et al 2007 ;den Engelsman et al 2013 ;Marunouchi et al 2013 ;Nakagawa et al 2001 ;van den IJssel et al 2003 ). Since Drosophila sHsps are localized in different compartments, it has long been thought that their shuttling to other cellular compartments was not needed.…”
Section: Intracellular Localizationmentioning
confidence: 99%
“…Analysis of the CG43851 sequence predicts nuclear or cytoplasmic localization depending on the prediction tool used (Euk-mPLoc 2.0 (Chou and Shen 2010 ), SLP-Local (Matsuda et al 2005 ), CELLO v2.5 (Yu et al 2006 ), Sherloc2 ), MultiLoc2 . In mammals, all sHsps are mainly located in the cytoplasm but some shuttle to the nucleus or to the mitochondria (Bryantsev et al 2007 ;den Engelsman et al 2013 ;Marunouchi et al 2013 ;Nakagawa et al 2001 ;van den IJssel et al 2003 ). Since Drosophila sHsps are localized in different compartments, it has long been thought that their shuttling to other cellular compartments was not needed.…”
Section: Intracellular Localizationmentioning
confidence: 99%
“…It is believed that this prevents translocation of Bcl2 into the mitochondria, repressing Bcl2 antiapoptotic ability [38], thereby limiting cell immortality and cancer pathogenesis. Dual phosphorylation at Ser59 in conjunction with Ser45 induced by PAR-2 activation has also been implicated in the protection of astrocytes against cytotoxic stress induced with C2-ceramide and staurosporine [49], and in the formation of nuclear speckles in HeLa cells [47,48]. It was reported that aB phosphorylated at Ser59 interacts with Gemin-3, part of the Survival Motor Neuron complex [48], and is translocated into the nucleoplasm where phosphorylation at Ser45 is involved in speckle formation [47].…”
Section: Roles Of Phosphorylated Aa and Abmentioning
confidence: 99%
“…Dual phosphorylation at Ser59 in conjunction with Ser45 induced by PAR-2 activation has also been implicated in the protection of astrocytes against cytotoxic stress induced with C2-ceramide and staurosporine [49], and in the formation of nuclear speckles in HeLa cells [47,48]. It was reported that aB phosphorylated at Ser59 interacts with Gemin-3, part of the Survival Motor Neuron complex [48], and is translocated into the nucleoplasm where phosphorylation at Ser45 is involved in speckle formation [47]. Nuclear speckles act as depots to ensure a readily available source of chaperone in the event of cellular stress, upon which aB is then released from the speckles to prevent cell death [48].…”
Section: Roles Of Phosphorylated Aa and Abmentioning
confidence: 99%
See 2 more Smart Citations